2018
DOI: 10.1103/physrevlett.121.143601
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Correlated Photon Transport in Waveguide Quantum Electrodynamics with Weakly Coupled Emitters

Abstract: We show that strongly correlated photon transport can be observed in waveguides containing optically dense ensembles of emitters. Remarkably, this occurs even for weak coupling efficiencies. Specifically, we compute the photon transport properties through a chirally coupled system of N two-level systems driven by a weak coherent field, where each emitter can also scatter photons out of the waveguide. The photon correlations arise due to an interplay of nonlinearity and coupling to a loss reservoir, which creat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 61 publications
5
74
0
Order By: Relevance
“…Recently, the efficient coupling of atoms to nanophotonic structures in low dimensions [34] has enabled the study of almost perfectly one-dimensional systems that show infinite-range interactions [35] but also exotic chiral, coherent light-matter interactions which depend on the polarization of the incoming light [36]. Such waveguides have a high potential to generate nonclassical states of light [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the efficient coupling of atoms to nanophotonic structures in low dimensions [34] has enabled the study of almost perfectly one-dimensional systems that show infinite-range interactions [35] but also exotic chiral, coherent light-matter interactions which depend on the polarization of the incoming light [36]. Such waveguides have a high potential to generate nonclassical states of light [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…The lateral dimension of the entire circulator can be a few millimeters [39]. These properties make our chiral interface highly attractive for, e.g., on-chip routing of microwave signals [10,[14][15][16][17][18][19][20][21][22][23]36,37] as well as fundamental studies of chiral waveguide QED [3,4,7,46].…”
Section: (C) (Including the Separation D)mentioning
confidence: 99%
“…For instance, Jones et al have shown that collective effects arising from a 10-15 QE chain can result in a near-perfect chiral light-matter interaction [42]. Mahmoodian et al reported that strongly correlated photon emission can be achieved in optically dense emitter ensembles chirally coupled to waveguides even with weak coupling strengths [43]. And Mukhopadhyay and Agarwal have discussed the possibility of achieving perfect transparency in a chain of an even number of nonidentical QEs coupled to a waveguide with separation equal to a halfintegral multiple of resonant wavelength [44].…”
Section: Routing Improvement Due To Collective Effects Of Multiplementioning
confidence: 99%